Development of Anti-Dandruff Shampoo from Kaffir Lime which is the By-Product of Food Industry - Prasart Foo-trakul; Chonlada Watchiradatsatiean (Agriculture and Natural Resources, 2005)
Kaffir lime juice is a by-product of food industry. It could be used as an ingredient to make kaffir lime shampoo. The crude extract of kaffir lime oil from its peel could inhibit the growth of Candida alcicans which is a micro-organism associated with the dandruff of the scalp. The minimum inhibition concentration (MIC) of C. albicans by the oil was 1% (v/v). The kaffir lime juice has acid properties, helps cleaning hair, removes dirt and gives shampoo color. The optimum formula was kaffir lime juice, kaffir lime peel oil, sodium lauryl ether sulfate, coconut diethanolamide, 5-bromo-5-nitro-1, 3-dioxane (Bronidox) and water at 15.0, 1.0, 50.0, 30.0, 0.l and 30.0 % (w/w), respectively. A test with one hundred consumers showed that most of them were quite satisfied with this product especially in reducing dandruff of the scalp. The kaffir lime shampoo has color in L, a and b values of 4.6, -0.67 and 1.0, respectively. Its viscosity was 1,811 centipoise.